Assessment of polycyclic aromatic hydrocarbons in indoor and outdoor air of preschool environments (3-5 years old children) - Klara Slezakova (2016)
This work characterizes levels of polycyclic aromatic hydrocarbons (PAHs) in indoor and outdoor air of preschool environments, and assesses the respective risks for 3-5-years old children. Eighteen gaseous and particulate (PM1 and PM2.5) PAHs were collected indoors and outdoors during 63 days at preschools in Portugal. Gaseous PAHs accounted for 94-98% of total concentration (Sigma(PAHS)). PAHs with 5-6 rings were predominantly found in PM1 (54-74% particulate Ip pus). Lighter PAHs originated mainly from indoor sources whereas congeners with 4-6 rings resulted mostly from outdoor emissions penetration (motor vehicle, fuel burning). Total cancer risks of children were negligible according to USEPA, but exceeded (8-13 times) WHO health-based guideline. Carcinogenic risks due to indoor exposure were higher than for outdoors (4-18 times).